Structural behavior of negative moment region NSM-CFRP strengthened RC T-beams with various embedment depth under monotonic and cyclic loading. (1st December 2022) - Haryanto, Yanuar; Hsiao, Fu-Pei; Hu, Hsuan-Teh; Lie Han, Ay; Wiranata Chua, Andre; Salim, Fernando; Nugroho, Laurencius
Abstract: Under cyclic loading circumstances, reinforced concrete (RC) constructions may be subject to failure. Because they may indicate inadequate capacity owing to aging, environmental effects, or unintentional impacts, strengthening is critical to resist static and cyclic loads. Therefore, the goal of this research was to look at how bare and negative moment region strengthened RC T -beams behaved under monotonic and low reversed cyclic loads. As the strengthening system, carbon fiber reinforced polymer (CFRP) rods having different embedment depths were used with a near-surface mounted (NSM) approach. The findings of this study demonstrated that the impact of NSM-CFRP rods was sufficient for extending the ultimate load and capturing cracks under monotonic loading. Additionally, as compared to their bare counterparts, the negative moment region NSM-CFRP strengthened beams showed improved hysteresis behavior, a larger energy dissipation capacity together with initial stiffness, and a reduced damage index under cyclic loading. Moreover, the experimentally determined load-carrying capacities matched reasonably well with the theoretical predictions.